Association of fractional exhaled nitric oxide with asthma morbidity in urban minority children. (4th March 2023) - Chen, Laura; Agalliu, Ilir; Roth, Adam; Rastogi, Deepa
Abstract: Objective: Fractional exhaled nitric oxide (FeNO) is a well-established measure of allergic airway inflammation and possible useful adjunct disease management tool. We investigated the association of baseline and follow-up FeNO measurements with disease burden in minority children with persistent asthma. Methods: A retrospective chart review was conducted on 352 African American and Hispanic children seen at an urban Asthma Center in Bronx, NY. Demographic, clinical characteristics, and pulmonary function tests (PFTs) were compared between children with low, intermediate, and high baseline FeNO levels. Among 95 children with subsequent follow up visits, associations of change in FeNO with demographics, clinical characteristics, and PFTs were examined using mixed effects linear regression models. Results: A higher proportion of children with intermediate (54%) and high FeNO (58%) levels had lower airways obstruction compared to those with low FeNO levels (33%). Children with intermediate FeNO levels had more annual hospitalizations (2.8 ± 6.2) compared to those with low and high FeNO levels (1.3 ± 2.8 and 1.3 ± 2.5). These associations did not differ between ethnicities. An increase in FeNO over time was associated with higher BMI z-scores (β = 6.2, 95% CI: 1.0 to 11.4) and two or more hospitalizations in the past year (β = 16.1, 95% CI: 1.5 to 30.8). Conclusions: Intermediate and high FeNO levels are associated with lower airways obstruction and hospitalizations. Initial and serial FeNO measurements can be a useful adjunctive tool in identifying asthma-related morbidity in urban African American and Hispanic children.